The Impacts of Rajab Celebration Culture on Social Communities in Turkey - Azhari (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2021)
Introduction: Etymologically, Rajab derives from a Semitic root that refers to the act of consecration and glorification. The verb tarjīb means to glorify and sanctify someone or something. The first Hadith: “Rajab is the month of Allah, Shac bān is my month and Ramaḍān is my people’s month.but do not ignore the first Friday night in Rajab. Methods: This research is a qualitative type, using methods of interviews, in-depth interviews and observations. Here's the research flow framework, Data was obtained from everyone who participated in the celebration. Results: Based on the data obtained from the community and the observation found that with the celebration of Rajab culture has made a positive influence on the social life of society. Conclusion: Based on the results of the study showed that the culture of Rajab celebration has had positive influences, including the availability of space to socialize and exchange ideas, increase social awareness, become social recreation spaces that eliminate urban stress.